Máscaras reales y fragmentadas de Buenos Aires. - Baisotti, Pablo (Theory in Action, 2022)
This article presents a vision of the city of Buenos Aires through some novels and short stories created by Argentine writers, in which their characters use "masks" to face reality or, in some cases, fiction. The various characters have masks used to disguise their identities in their relationship with other people and to hide their feelings. The time used to analyze these issues will be: 1) the "real" time, that is, the action that takes place in a linear and continuous time and; 2) a "fragmented" time, represented in two or more levels in which reality and fiction are superimposed and even, at a certain point, confused. The city is the background frame where the real and the illusory meet through the characters of Adolfo Bioy Casares, Leopoldo Marechal, Julio Cortázar, Ernesto Sábato, Marco Denevi, Pedro Orgambide, among others.